2021
DOI: 10.11648/j.ijse.20210501.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Super White Washing Process Temperature and Optical Brightening Agent Concentration on Various Properties of Stretch Denim Fabric

Abstract: This research work was intended to discover the effect of super white washing process temperature and OBA (optical brightening agent) concentration on various properties of stretch denim fabric. Different properties like tensile strength, tear strength, dimensional stability, pilling resistance, hand feel performance, color fastness to washing, color fastness to perspiration, color fastness to light were investigated. All experimental tests were carried out according to the ISO (International Organization for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Like one of the studies reported significant variation in shrinkage after ozone treatment [8]. Whereas spandex fibre shrinks more in hot environment in the garments during washing and drying processes [7].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Like one of the studies reported significant variation in shrinkage after ozone treatment [8]. Whereas spandex fibre shrinks more in hot environment in the garments during washing and drying processes [7].…”
Section: Introductionmentioning
confidence: 82%
“…It is very important to investigate shrinkage of stretchable denim on different drying temperatures too because elastin shrinks more in hot environment. An investigation reported -0.9% and -1.9% shrinkage in warp and weft respectively at 35°C, however with gradual rise of process temperature; it increased to -3.1% and -4.7% at 80°C [7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the report of BGMEA, the highly competitive scenarios in apparel trade and frequent trade wars had caused a declined trend at 1.6% apparel trade from . During COVID-19 pandemic (2019-2021, the world's demand of apparels has been decreasing day by day, which forces the manufacturers and suppliers to export at 50% -60% lower prices. That's why, the RMG experts and prominent economists suggested that both product and market diversification is a must for the existence of the economy, if the country wants to explore its current lead in global apparel export, just after post pandemic situation.…”
Section: Product and Market Diversificationmentioning
confidence: 99%
“…That's why, the RMG experts and prominent economists suggested that both product and market diversification is a must for the existence of the economy, if the country wants to explore its current lead in global apparel export, just after post pandemic situation. Bangladesh depends on five items such as men's and women's t-shirt, trouser, shirt, jacket and sweater for export while Vietnam has diversified its product line (Rahaman et al, 2021b;Hasan et al, 2021). Only in a single market, Vietnam exports 10 types of products in USA, including women's knit shirts and blouses (MMF), women's trousers (cotton), women's knit shirts and blouses (cotton), women's trousers (MMF), men's knit shirts (cotton), dresses (MMF), men's trousers (MMF), men's knit shirts (MMF), men's trousers (cotton), and women's coats (MMF).…”
Section: Product and Market Diversificationmentioning
confidence: 99%